Electrophile induced branching cascade: a powerful approach to access various molecular scaffolds and their exploration as novel anti-mycobacterial agents - Patil, Nitin T.; Konala, Ashok; Sravanti, Sudha; Singh, Ashita; Ummanni, Ramesh; Sridhar, Balasubramanian (Chemical Communications, 2013)
Herein we report on the Electrophile Induced Branching Cascade (EIBC), a new technique to produce a variety of biologically important molecular scaffolds. Some compounds exhibit excellent activities against Mycobacterium smegmatis.